Simple and sensitive procedure for screening yeast mutants that lyse at nonpermissive temperatures. - Cabib, E (J Bacteriol, 1975)
After mutagenesis, surviving yeast cells are grown on plates at 25 C and later exposed to 37 C. The plates are then overlaid with a soft agar containing p-nitrophenylphosphate at pH 9.7. Lysed cells liberate alkaline phosphatase which gives rise to a yellow color on and around colonies. IMAGES: